2021
DOI: 10.1136/bmjopen-2020-043890
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of contraceptive use among sexually active unmarried adolescent girls and young women aged 15–24 years in Ghana: a nationally representative cross-sectional study

Abstract: ObjectiveThere is a decline in contraceptive use among sexually active unmarried young women in Ghana. This study assessed the prevalence of contraceptive knowledge and use, and the determinant of contraceptive use among sexually active unmarried young women in Ghana.DesignThis was a nationally representative cross-sectional survey, using data from the 2017 Ghana Maternal Health Survey. Weighted logistic regression was used to assess the association between background and obstetric characteristics of young wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
(25 reference statements)
8
18
1
Order By: Relevance
“…In the final model after adjusting with other variables, contraceptive use was higher among respondents with high education compared to respondents with middle and primary education (PR 1.51, 95% CI 1.09 -2.07, p=0.012). This finding is in accordance with another study which revealed that respondents with secondary education (Senior High School) possessed higher contraceptive use compared to those with basic education (Oppong et al, 2021). Another finding also discovered that women were less likely to use inconsistent condoms compared to primary, secondary and tertiary education.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In the final model after adjusting with other variables, contraceptive use was higher among respondents with high education compared to respondents with middle and primary education (PR 1.51, 95% CI 1.09 -2.07, p=0.012). This finding is in accordance with another study which revealed that respondents with secondary education (Senior High School) possessed higher contraceptive use compared to those with basic education (Oppong et al, 2021). Another finding also discovered that women were less likely to use inconsistent condoms compared to primary, secondary and tertiary education.…”
Section: Resultssupporting
confidence: 90%
“…The significant use of contraceptives among adolescents with higher education is due to the fact that they obtain correct information about the benefits of the usage of contraceptives. Education also encourages young women to determine greater consideration about their sexual and reproductive health (Oppong et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 ] Patel AA,[ 11 ] Gupta et al .,[ 13 ] Kumar N, et al .,[ 17 ] and Oppong FB, et al . [ 18 ] Improving education status can pave way to delay a women's marriage age, she will be able to seek a job and can help to change the attitude toward birth spacing and family size and empowers women to make a better decision.…”
Section: Discussionmentioning
confidence: 99%